Effects of sugar cane extract on steroidogenesis in testicular interstitial cells of male Japanese quail (Coturnix japonica). Issue 7 (12th June 2022) - Pu, Shaoxia; Kobayashi, Shohei; Mizu, Masami; Furuta, Toma; Nagaoka, Kentaro; Gore, Andrea C.; Crews, David; Watanabe, Gen
Abstract: Sugar cane extract (SCE) is the end product of glucose, fructose, and sucrose elimination in molasses. SCE has various biological effects, such as anti‐inflammation and antioxidation, and it is commonly found in animal feed. The present research is aimed at investigating the reproductive endocrine influence of SCE in male Japanese quails ( Coturnix japonica ) by feeding SCE containing food. In addition, in vitro Leydig cell culture was conducted to clarify the mechanism of SCE's influence. Our results showed that SCE feed extended the latency to the first neck grab, decreased male quail testis and epididymis weights, cloaca gland size, and reduced serum testosterone concentrations. Steroidogenic enzymes 3βHSD, 17βHSD, P450c17, and P450scc gene expression in the testis were decreased in the SCE groups. Western blot analysis showed decreased 3βHSD in the testis after feeding SCE. Isolated testicular interstitial cells cultured with SCE and ovine‐LH suppressed testosterone secretion and 3βHSD gene expression. In conclusion, SCE as a feed additive has an impact on the sexual behavior and reproductive function of male Japanese quail, with the suppression of steroidogenesis in the Leydig cell. Our results may provide beneficial information to the livestock management and the poultry industry. Abstract : We found that sugar cane extract decreased serum testosterone through decreased 3βHSD in male Japanese quails. Research highlights: Sugar cane extract (SCE) influences the sexual behavior of male quail. SCE decreases testosterone production and 3βHSD expression in the testis.